2010
DOI: 10.1016/j.jbankfin.2009.11.013
|View full text |Cite
|
Sign up to set email alerts
|

CAPM and APT-like models with risk measures

Abstract: a b s t r a c tThe paper deals with optimal portfolio choice problems when risk levels are given by coherent risk mea sures, expectation bounded risk measures or general deviations. Both static and dynamic pricing models may be involved. Unbounded problems are characterized by new notions such as (strong) compatibility between prices and risks. Surprisingly, the lack of bounded optimal risk and/or return levels arises for important pricing models (Black and Scholes) and risk measures (VaR, CVaR, absolute devia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 36 publications
0
11
0
1
Order By: Relevance
“…3 In particular, ρ (y 0 ) = 0 for every G-deviation ρ and every y 0 ∈ Lp (μ G , E). Notice that it is sufficient to impose ρ to be (Λ, G)-translation invariant and positively homogeneous.…”
Section: Definition 32mentioning
confidence: 99%
“…3 In particular, ρ (y 0 ) = 0 for every G-deviation ρ and every y 0 ∈ Lp (μ G , E). Notice that it is sufficient to impose ρ to be (Λ, G)-translation invariant and positively homogeneous.…”
Section: Definition 32mentioning
confidence: 99%
“…Balbás et al (2010) proposed a general optimal investment problem with coherent and expectation bounded risk measures and perfect pricing models. The natural extension for a market with friction is Good deals in markets with friction 5 minimizes the risk of a pay-off y whose global ask price is not higher than one dollar and whose expected value is at least R. Thus, it is a standard risk/return approach with ρ as the risk measure.…”
Section: Primal and Dual Optimal Investment Problemsmentioning
confidence: 99%
“…Balbás et al (2010) 40 have shown the existence of 'pathological results' when combining some risk measures (VaR, CVaR, dual power transform (DPT), etc.) and very popular pricing models (Black and Scholes, Heston, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Rockafellar, Uryasev, and Zabarankin (2007) use the so-called diversion measures (an example is Conditional Value at Risk, CVaR) to investigate equilibrium in capital markets. Balbás, Balbás, and Balbás (2010) use coherent risk measures, expectation bounded risk measures and general deviations in optimal portfolio problems, and study CAPM-like relations. Grechuk and Zabarankin (2012) consider an optimal risk sharing problem among agents with utility functionals depending only on the expected value and a deviation measure of an uncertain payoff.…”
Section: Introductionmentioning
confidence: 99%